GASP XXXIX: MeerKAT hunts Jellyfish in A2626. Issue 2 (6th September 2022) - Deb, Tirna; Verheijen, Marc A W; Poggianti, Bianca M; Moretti, Alessia; van der Hulst, J M; Vulcani, Benedetta; Ramatsoku, Mpati; Serra, Paolo; Healy, Julia; Gullieuszik, Marco; Bacchini, Cecilia; Ignesti, Alessandro; et al.
ABSTRACT: We present MeerKAT H i observations of six jellyfish candidate galaxies (JFCGs) in the galaxy cluster, A2626. Two of the six galaxies JW100 and JW103, which were identified as JFCGs from B-band images, are confirmed as jellyfish galaxies (JFGs). Both of the JFGs have low H i content, reside in the cluster core, and move at very high velocities (∼ 3σ cl ). The other JFCGs, identified as non-jellyfish galaxies, are H i rich, with H i morphologies revealing warps, asymmetries, and possible tidal interactions. Both the A2626 JFGs and three other confirmed JFGs from the GASP sample show that these galaxies are H i stripped but not yet quenched. We detect H i, H α, and CO(2-1) tails of similar extent (∼50 kpc) in JW100. Comparing the multiphase velocity channels, we do not detect any H i or CO(2-1) emission in the northern section of the tail where H α emission is present, possibly due to prolonged interaction between the stripped gas and the intracluster medium. We also observe an anticorrelation between H i and CO(2-1), which hints at an efficient conversion of H i to H2 in the southern part of the tail. We find that both ram-pressure stripping and H i -to-H2 conversion are significant depletion channels for atomic gas. H i -to-H2 conversion is more efficient in the disc than in the tail.